1997
DOI: 10.1346/ccmn.1997.0450403
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Randomly Mixed-Layered Chlorite/Smectite in the Transformation of Smectite to Chlorite

Abstract: Abstract--Vesicular and groundmass phyllosilicates in a hydrothermally altered basalt from the Point Sal ophiolite, California, have been studied using transmission electron microscopy (TEM). Pore-filling phyllosilicates are texturally characterized as having coherent, relatively thick and defect-free crystals of chlorite (14 _A) with occasional 24-.~ periodicities. Groundmass phyllosilicates are texturally characterized as 1) randomly oriented crystals up to 200 A in width and 2) larger, more coherent crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…%S value for each decomposed peak from peak position and the working curve of Eq. (2) are also shown a processes proposed by Bettison-Varga and Mackinnon (1997) that leads to the release of fluids, thus contributing to the bulk dehydration of oceanic basalts. Here, we use the Nankai subduction zone as a case study to examine the possible dehydration of underthrusting basalts.…”
Section: Dehydration Of Underthrust Basalts As a Results Of S-c Convermentioning
confidence: 83%
“…%S value for each decomposed peak from peak position and the working curve of Eq. (2) are also shown a processes proposed by Bettison-Varga and Mackinnon (1997) that leads to the release of fluids, thus contributing to the bulk dehydration of oceanic basalts. Here, we use the Nankai subduction zone as a case study to examine the possible dehydration of underthrusting basalts.…”
Section: Dehydration Of Underthrust Basalts As a Results Of S-c Convermentioning
confidence: 83%
“…Higher substitutions of octahedral Fe 2+ for Mg 2+ in the chlorites may compensate for the distortions introduced by the substitution of the larger A13+ cation for Si 4+ in the tetrahedral sheet (Shau et al, 1990). However, Hillier (1993), Bettison-Varga et al (1991), andMackinnon (1997) found no changes in the Fe/Mg ratio of coexisting chlorites and corrensites. Our results indicate a clear difference between chlorite and corrensite compositions, with well-defined ranges for each phase (Figures 4 and 5).…”
Section: Compositional Variations Of Chlorite and Corrensitementioning
confidence: 89%
“…Bettison-Varga and Mackinnon (1997), in a study of trioctahedral phyllosilicates from the Point Sal ophiolite, showed lattice fringe images of very thick (50 unit cells?) C-S (R0) with a composition -50% chlorite.…”
Section: Discussionmentioning
confidence: 99%
“…Finegrained phyllosilicates are perhaps the most abundant alteration product. As a consequence, they have been studied extensively to document changes in mineral structure and composition that could aid in reconstructing the geologic history of the alteration process (Kristmannsdottir, 1979;Bettison and Schiffman, 1988;Schiffman and Fridleiffson, 1991;Robinson et al, 1993;Shau et aL, 1990;Shau and Peacor, 1992;Schiffman and Staudigel, 1995;Bettison-Varga and Mackinnon, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation